History of creation, aims and tasks of Turkestan section of archeology amateurs (Journal of history, 2019)
In this article, history of creation, aims and tasks of scientific social organization are considered of the Turkestan section of archeology amateurs.From the second half of XIX century to the beginning of XX century – the period of great development of the scientific idea.In this process social scientific organizations which are created in Saint Petersburg and whole Central Asia countries which were in the content of Russian Empire played major role. Most of them became important scientific organizations, which are systematically organizing excavations, research, restoration and protecting ancient statues and published work in different periodical press.One of these organizations was Turkestan section of archeology amateurs which was created in 1895 in Tashkent.Turkestan section of archeology amateurs were scientific regional organization, which studied ancient statues of Central Asia during 20 years.Education of this scientific society allowed widespread development of research of archeological statues.